Status and Progress in Cross-Border Portability of Social Security Benefits - Robert Holzmann; Jacques Wels (Institute of Labor Economics (IZA), 2018)
The importance of cross-border portability of social benefits is increasing in parallel with the rise in the absolute number of international migrants and their share of the world population, and perhaps more importantly, with the rising share of world population that for some part of their life is working and/or retiring abroad. This paper estimates how the rising stock of migrants is distributed over four key portability regimes: those with portability through bilateral social security arrangements (regime I); those with potential exportability of eligible benefits from abroad (regime II); documented workers with no access to national schemes but no contribution payment either (regime III); and undocumented workers with no access to any scheme (regime IV). Estimates for 2000 and 2013 are compared. The results indicate a modest but noticeable increase in the share of migrants under regime I, from 21.9 percent in 2000 to 23.3 percent in 2013. The biggest change occurred under regime III, which almost doubled to 9.4 percent. Regime II reduced by 3.0 percentage points but remains the dominant scheme (at 53.2 percent). The estimates suggest that the scope of regime IV (informality) reduced by 2.9 percentage points, accounting for 14.0 of all migrants in 2013. This trend is positive, but more will need to be done to progress on benefit portability.
Keywords: D69; H55; I19; J62; 330; labor mobility; retirement mobility; portability regimes; bilateral social security agreements; social benefits